Social Security for Women Workers in Unorganized Sector (International Journal of Food and Nutritional Sciences, 2022)
In India it can be said that the Unorganized Sector play a major role in providing employmentopportunities and contribute to nearly 80% of GDP. Unorganized sector helps to solve theproblem of unemployment. Unorganized sector provides employment to the largest numberof people women participation in this industries is more than men. This research paper studythe social security for women workers in unorganized sector.